PERAN KOMPONEN BIOAKTIF DALAM SENYAWA ALAMI UNTUK TATALAKSANA HEPATITIS - Aulia Berliana; Graharti, Risti (CV. Jasa Sukses Abadi, 2024)
Hepatitis virus infection is a global public health threat that causes substantial liver-related morbidity and mortality. Hepatitis is a liver infection that causes inflammation, causing swelling of the liver. This liver infection has various variants, all of which are detrimental to human health. In recent times, natural compounds have become popular to be developed as antiviral drugs to fight viral infections. These natural compounds can come from plant extraction or a combination of animal and plant extraction. Several of these compounds have shown significant effectiveness in their mechanism as antivirals against the hepatitis virus due to the presence of bioactive components in them. The mechanism of action of this bioactive component is demonstrated by disrupting the virus life cycle, replication, release, and interaction with the host. This literature study will explain strategies for treating hepatitis with these natural compounds. Recent research shows that bioactive components such as phenylpropanoids, flavonoids, xanthones, anthraquinones, terpenoids, alkaloids, and aromatics have antiviral activity against hepatitis. Therefore, based on a literature review of the latest research that reveals clinical trials of these bioactive components, this natural compound can be used as a potential treatment alternative in the management of hepatitis in the future.